(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Woman should be considered as a most important valuable jewel as the four fold objectives of life, progeny, happiness, all can be attained only through her. Her life is spread into different stages due to some anatomical and physiological changes in body. She responds very differently in different stages of her lives. Menopause is a natural phase which tends to be highly variable in timings, pattern and behavior due to the reduction in reproductive sex hormones. Symptoms associated with menopause are mood changes, hot flushes, emotional changes, sleep disturbance, dry skin and hair, aches and pains in joints known for the negative effects on the quality of life of many women. Yoga encourages woman to know her woman hood & express her feminine energy and power and giving her enough knowledge to use them on a day by day basis. While knowing and caring for herself in times of vulnerability she can maintain her individuality, energy, respect, power & health applying the principles of Yoga to her own individual situation. Asana and Pranayama have a far reaching effect upon body and mind. Pranayama is the practice of breath control, and Asana is the practice of physical postures. Therefore, combining these two elements make for ultimate Yoga practice. Yoga can be helpful to manage the changes in body from puberty to menopause. It makes the changes less painful and improve immunity and resistance to handle changes naturally.